(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT The Arabic language has been given a great honour. Allah Almighty revealed the Great Qur’an in its clear language, and Allah Almighty has chosen it from among the languages ​​of all human beings. In the revelation of the Noble Qur’an in the Arabic language, there is a high rank for the science of Arabic, and from here we find a close and inextricable link between it and all Islamic and non-Islamic sciences, we do not exaggerate if we say that it is the first key to understanding these sciences and their main focus, and among these great sciences is the science of jurisprudence, which is the balance of justice in the statement of the legal rulings of all Islamic doctrines, and for this the focus of my research will be to clarify this connection through a part - with a wide and important area in The Arabic language - that is, the truth and metaphor, with the knowledge of the principles of jurisprudence and the use of these two words together or not, and their impact on the process of deduction and the manifestation of rulings. This makes us take the Arabic language as a means to understand the provisions of the Noble Qur’an through the Verified bys of the principles of jurisprudence . Without it, the Holy Quraan remains closed from understanding, and he has no luck except the recitation of the tongue. There is no doubt that this is not what is meant by revelation Allah says: (kitab anzilnah alik mubarak liudabiruu ayatih waliatadhakar awluu alalbab) [p.: 29] In the realm of the will of the two meanings, both real and figurative, a fundamental disagreement occurred.